A Review of Socio-Cultural Theory - Mahbobeh Rahmatirad (Budapest International Research and Critics University, 2020)
The purpose of this study is to explore Vygotsky’s contribution to the socio-cultural theory in the field of education in general. Socio-Cultural Theory, based on Vygotskian thought, is a theory about the development of human cognitive and higher mental function. The theory specially emphasizes the integration of social, cultural and biological elements in learning processes and stresses the socio-cultural circumstances’ central role in human’s cognitive development. The study aims to elaborate the impact of social-cultural theory in the leaning. The study also reviews implications and applications of socio-cultural theory in second language acquisition. Moreover, this study also critiques the strong points and weakness points of this theory. There are a number of language learning theories which are introduced by researchers in second language research. These theories are based on research and observation in the field of language learning. B. F Skinner’s theory of behaviorism, Chomsky’s theory of Universal Grammar, Krashen’s five Hypotheses, connectionism and Vygotsky’s socio-cultural theory have changed people’ mind of language learning.